2017
DOI: 10.21608/jpp.2017.42014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Bread Wheat Genotypes under Saline Soil Conditions Using Tolerance Indices and Multivariate Analysis

Abstract: The present investigation was conducted in a field experiments at Sakha Agricultural Research Station Farm to evaluate 24 bread wheat genotypes during the two growing seasons 2014/2015 and 2015/2016 under normal and salinity stress conditions. The experimental design used was a randomized complete block design with three replicates. Eleven stress tolerance indices (STI's) were calculated based on average grain yield under normal and stress conditions across the two seasons. Moreover, cluster analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
10
4
0
Order By: Relevance
“…As indicated in (table 2), variations in rainfall quantity and distribution between the two seasons caused a differential response of genotypes to salinity levels. Similar findings were reported by Dhayal & Sastry (2003); El-Hendawy et al (2005); Darwish et al (2017) and Gadallah et al (2017). Salinity levels effect: Means presented in (table 5) revealed that days to maturity and grain filling period increased significantly at moderate salinity compared to the control.…”
Section: Resultssupporting
confidence: 90%
“…As indicated in (table 2), variations in rainfall quantity and distribution between the two seasons caused a differential response of genotypes to salinity levels. Similar findings were reported by Dhayal & Sastry (2003); El-Hendawy et al (2005); Darwish et al (2017) and Gadallah et al (2017). Salinity levels effect: Means presented in (table 5) revealed that days to maturity and grain filling period increased significantly at moderate salinity compared to the control.…”
Section: Resultssupporting
confidence: 90%
“…Data indicated that Misr1 and Line 2 can be used in both normal and saline soil conditions. These results are in agreement with Darwish et al, 2017 andGadallah et al, 2017. Interaction effects A-Effect of years: Table (6) illustrates the average values of all studied characters combined across the two normal and saline soil conditions in the two seasons.…”
Section: Mean Performancesupporting
confidence: 92%
“…For grain yield reduction % the lowest values were recorded for Line 11, 14 and 2 (38.89, 41.54 and 44.81%), respectively. Similar finding were reported by Darwish et al (2017) and Yassin et al (2019). Tables 8 & 9 showed the interaction among saline soil conditions, seasons and genotypes for all studied characters.…”
Section: B-effect Of Saline Soil Conditionssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, Group D consisted of three genotypes G12, G8 and G5 that displayed the lowest values and subsequently these genotypes could be considered the highly sensitive ones. These results were in consistence with those of Bagci et al (2007), Ahmadi et al (2012), Asadi et al (2012), Badran andMoustafa (2014), Abd El-Mohsen et al (2015); Desheva and Kyosov (2015), Sanjay et al (2015), Sara et al (2015), Afiah et al (2016), Darwish et al (2017), Maha et al (2017), Yassin, et al (2019 and Gadimaliyeva et al (2020). Yp is grain yield under 6000 ppm, Ys is grain yield under 9000 ppm, SSI is stress sensitivity index, MP is mean productivity, GMP is geometric mean productivity, STI is stress tolerance index, YI is yield index and YSI is yield stability index.…”
Section: Salinity Tolerance Indices and Cluster Analysissupporting
confidence: 87%